Is Under-Consumption Responsible for Persistent Stagnation in the US Manufacturing Sector? Econometric Evidence and Implications for State Policy, 1965–2008. Issue 1 (2nd January 2016) - Ansari, Shaukat
ABSTRACT: The monopoly capital/under-consumption model of crisis posits that under conditions of oligopoly the system's inability to absorb a rising surplus generates reduced growth rates and, in the absence of counteracting mechanisms, stagnation. This paper argues that the theory's explanation for the crisis of manufacturing profitability that erupted in 1965 is not supported by the empirical data pertaining to profit rates, capacity utilization, and state expenditure. Specifically, the paper presents an econometric ARIMAX model which incorporates government expenditure as a control variable in order to test whether state spending serves as a counteracting mechanism to raise capacity and increase the manufacturing profit rate, as predicted by the monopoly capital school. It is argued that the model does not support the contention that system-wide stagnation is related to insufficient aggregate demand. Rather, the evidence suggests that the accumulation process continues to be governed by fierce competition. The implications of this conclusion for state policy and labor organizing are also discussed.